KOMPLIKASI PASKA TRANSPLANTASI GINJAL - Juliana, I Made; Sidharta Loekman, Jodi (journal of internal medicine; Vol. 8, No. 1 Januari 2007)
Renal transplantation is the take over of kidney from healthy person and then be transplanted to the other person who has severe and permanent kidney function disorder. Renal transplantation is the most effective treatment for terminal stage of chronic kidney disease. The survival of patients who underwent renal transplantation depend on some factors including screening of patients, pretransplantation management, surgery technic and management of patients after renal transplantation. Complications after renal transplantation devide to surgery complications and non surgery (medical) complications. Surgery complications are mayor complication such as bleeding and anaestesion drug effect and the other complications due to transplantation process. Medical complications are rejection (hyperacute, acute and chronic rejection), infection, cardiovascular disease, anemia, hypertension, diabetes mellitus, dislipidemia, hyperhomocysteinemia, malignancy, lymphoproliferative disease and psychological effect. Rejection is the most important complication. If hyperacute rejection ocured, kidney transplant must be take over to avoid more severe systemic inflammation respon. New generation of humanized IL-2 receptor antibody, daclizumab (zenapax) can decrease the incident of hyperacute rejection. Acute rejection can be treated with steroid, polyclonal antilymphocyte globulin, monoclonal antibody OKT3 and plasma exchange. Chronic rejection was difficult to treat. Immunosupresion agen have no much role because destroyed were occured. Prevention just to manage risk factors and then wait the other transplantation. For the other complications, the management based on etiology and the type of complication.
Keywords: renal transplantation, complications